GLOBAL PROBLEMS OF HUMANITY (American Journal of Research in Humanities and Social Sciences, 2023)
The article explores the global problems facing modern society. She emphasizes that these problems require the common efforts of all countries to solve them, since they affect the life of all humanity and determine the fate of civilization. The article points out the causes of global problems, such as contradictions and conflicts between people, as well as the responsibility of society for the consequences of technological progress. She presents several examples of specific global problems, such as interpersonal problems, problems in relations with nature and society, the problem of war and peace, environmental problems, problems of energy, climate, food and others. Particular attention is paid to the problem of thermonuclear war, which poses a serious threat to humanity. The article emphasizes that all environmental problems have a common root in human activities that negatively affect the environment.